2016
DOI: 10.2337/db15-1216
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Response to Drinking Glucose and Fructose in Obese Adolescents

Abstract: Increased sugar-sweetened beverage consumption has been linked to higher rates of obesity. Using functional MRI, we assessed brain perfusion responses to drinking two commonly consumed monosaccharides, glucose and fructose, in obese and lean adolescents. Marked differences were observed. In response to drinking glucose, obese adolescents exhibited decreased brain perfusion in brain regions involved in executive function (prefrontal cortex [PFC]) and increased perfusion in homeostatic appetite regions of the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 53 publications
3
53
0
Order By: Relevance
“…18 In the current small study, neither group showed significant modification in hypothalamic BOLD signal after glucose ingestion. This is consistent with a study including lean adolescents (N = 14) that demonstrated no change in hypothalamic perfusion after glucose ingestion 31 ; however, the same study reported increased perfusion in adolescents with obesity (N = 24). 31 In agreement with the latter, an increase in hypothalamic BOLD signal after glucose ingestion has also been described in a study with adults with obesity and lean subjects (total N = 21), 20 and two studies involving only normal-weight adults 18,32 (N = 18 and 7, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…18 In the current small study, neither group showed significant modification in hypothalamic BOLD signal after glucose ingestion. This is consistent with a study including lean adolescents (N = 14) that demonstrated no change in hypothalamic perfusion after glucose ingestion 31 ; however, the same study reported increased perfusion in adolescents with obesity (N = 24). 31 In agreement with the latter, an increase in hypothalamic BOLD signal after glucose ingestion has also been described in a study with adults with obesity and lean subjects (total N = 21), 20 and two studies involving only normal-weight adults 18,32 (N = 18 and 7, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Rodents also develop symptoms suggesting anxiety, stress, and withdrawal symptoms when sugar is removed and exhibit potentially harmful behaviours, such as crossing a shock grid, to regain access . An altered brain response to drinking glucose and fructose has also been reported in children with obesity . Despite convincing evidence presented, Dr. Avena addressed several common critiques challenging the concept of sugar addiction (Table ) .…”
Section: Seminar 2: Why Is Reducing Added Sugar Intake So Difficult?mentioning
confidence: 99%
“…In the binge eaters, naloxone reduced the preference for sweet taste and the actual amounts consumed. The findings of Jastreboff et al (9) that glucose and fructose stimulate the striatal system more in the adolescents with obesity than in lean individuals indicate that these molecules have addictive or habituating potential. In many cases sucrose is consumed in sugar-sweetened beverages that also contain caffeine, a drug that stimulates the central nervous system.…”
mentioning
confidence: 99%
“…The study by Jastreboff et al (9) describes functional differences in the central nervous system during response to fructose or glucose solutions. First, the executive center in the prefrontal cortex is inhibited in the obese, confirming earlier work in adolescents (11,12) and adults where Volkow et al (13) showed a significant negative correlation between BMI and metabolic activity in prefrontal cortex and cingulate gyrus.…”
mentioning
confidence: 99%
See 1 more Smart Citation